The Case of Adama Town Ring Road to Kidane- Mihiret Church through Derartu Square - Asia, Esa (ASTU, 2019)
Adama is strategic and a largest business corridor with a is high rate of in and out movement of peoples per day. This accounts poor street infrastructures provision on main streets of the Town. Higher conjunction and absence of pedestrian’s ways creates dissatisfaction of residents and street users. The study uses data collection methods like questionnaire, interview, focus group discussion and direct observation to get concrete and useful data for the research subject. General objective of the research is emanated from current problems existing in Adama Town Ring Road to Kidane-Mihiret Church through Derartu square and thus: to identify the major problems regarding street infrastructures planning and to look for better ways of plan and design preparation and implementation that suits the socio-economic and physical environment of the town in particular and the country in general. The major finding of this paper is the gap between plan formulating and approaches to realize street infrastructure planning, un-integration of various stake holders who work on infrastructure planning and expansion results chaotic environment which is not comfortable for residents and incurs unexpected cost on municipalities.
Keywords: Street Infrastructure, Roundabout, Drainage, Pedestrian